Painting by numbers: case studies in the economic history of nineteenth-century landscape and rural genre painting - Greenwald, D (2018)
Industrialization altered the socioeconomic landscapes of France and the United States in the nineteenth century; meanwhile, the content and style of art produced in both countries also changed. In particular, landscape and rural genre painting became more prominent. Scholars have argued that the socioeconomic changes caused the artistic ones. This thesis, “Painting by Numbers: Case Studies in the Economic History of Nineteenth-Century Landscape and Rural Genre Painting”, uses methods from the social sciences to conduct case studies that examine these causal links. In addressing this topic, this project engages with the work of T.J. Clark, Alan Wallach and other founding social historians of art. With the creation of two databases containing information about 410,000 artworks exhibited in nineteenth-century France and the U.S., this thesis applies statistical methods to a much larger sample of artistic data. Exploiting this data source provides a socioeconomic history of the average experience of participants in the art world rather than detailed examinations of the experiences of a handful of still-famous artists, which have been more typical of the field. The first two chapters of the thesis provide an introduction, literature review, and description of the French dataset. Chapters 3 and 4 address research questions in the history and historiography of images of nature in nineteenth-century French art. Chapter 3 employs econometrics to examine systematic relationships exist between the quantities of images of nature exhibited in nineteenth-century France and the pace of industrialization. Statistically, the element of modernization that most affected the output of images of nature in the artistic data examined was the founding of artists’ colonies near new rail lines connecting Paris to the countryside. Chapter 4 analyzes the artist Jean François Millet’s letters, excerpts of which scholars used to form assump- tions about how artists’ anti-urban attitudes inspired their depictions of nature. The chapter demonstrates that Millet was an active user of industrial modes of transport who often traveled to Paris. Chapter 5 introduces the American dataset, and the remaining chapters present three case studies about art in the U.S. during the nineteenth century. Chapter 6 examines the much-cited inventory The Art Treasures in America, showing it overstates the amount of European art in American collections during the nineteenth century. Chapter 7 analyzes how art collectors’ socioeconomic backgrounds influenced their acquisitions; it demonstrates that socioeconomic markers are generally poor predictors of collecting patterns. Chapter 8 investigates the relationship between the growth of the railroad in the U.S. and landscape painting. Mapping the frequency of depiction of natural sites alongside the growth of railroads shows that visual culture is often a byproduct of rail lines built for other purposes rather than a catalyst for building new lines. My thesis refines current understanding of how socioeconomic change affected art in the nineteenth century in two ways. First: it shows sample bias can compromise existing socioeconomic histories of art, and the use of data can help combat this bias. Second: it provides examples of how industrialization most affected artistic output by removing structural constraints on the geographic movement of artists, collectors and artworks themselves. More broadly, this project demonstrates that scholars can use digital tools in conjunction with economic methods to document and analyze phenomena in the art history that would be neglected in purely qualitative analyses.